Analysis for the welding crack leakage of deethanizer. Issue 3 (April 2021) - Jiang, Chengjun; Wang, Xin; Xue, xiaolong; Du, Yannan; Wang, Wei
Abstract: A deethanizer made of 16MnDR steel was found medium leakage used by a company shortly after weld repair. The cause of the welding crack leakage was analyzed by means of morphology examination, chemical composition analysis and hardness test, residual stress test, metallographic examination, and microscopic metallographic analysis. The results show that the crack produced by the 16MnDR pressure vessel after weld repair is a typical liquefaction crack of weld metal. Improper control of repair operation process results in abnormal microstructure, excessive hardness and excessive residual stress at repair welding position, which leads to the formation of longitudinal microcrack, and further expansion in use to form penetrative crack leakage.